A Validated Risk Score for Venous Thromboembolism Is Predictive of Cancer Progression and Mortality. (28th April 2016) - Kuderer, Nicole M.; Culakova, Eva; Lyman, Gary H.; Francis, Charles; Falanga, Anna; Khorana, Alok A.
Abstract : Background: Retrospective studies have suggested an association between cancer-associated venous thromboembolism (VTE) and patient survival. We evaluated a previously validated VTE Clinical Risk Score in also predicting early mortality and cancer progression. Methods: A large, nationwide, prospective cohort study of adults with solid tumors or lymphoma initiating chemotherapy was conducted from 2002 to 2006 at 115 U.S. practice sites. Survival and cancer progression were estimated by the method of Kaplan and Meier. Multivariate analysis was based on Cox regression analysis adjusted for major prognostic factors including VTE itself. Results: Of 4, 405 patients, 134 (3.0%) died and 330 (7.5%) experienced disease progression during the first 4 months of therapy (median follow-up 75 days). Patients deemed high risk ( n = 540, 12.3%) by the Clinical Risk Score had a 120-day mortality rate of 12.7% (adjusted hazard ratio [aHR] 3.00, 95% confidence interval [CI] 1.4–6.3), and intermediate-risk patients ( n = 2, 665, 60.5%) had a mortality rate of 5.9% (aHR 2.3, 95% CI 1.2–4.4) compared with only 1.4% for low-risk patients ( n = 1, 200, 27.2%). At 120 days of follow-up, cancer progression occurred in 27.2% of high-risk patients (aHR 2.2, 95% CI 1.4–3.5) and 16.4% of intermediate-risk patients (aHR 1.9, 95% CI 1.3–2.7) compared with only 8.5% of low-risk patients ( p < .0001). Conclusion: The Clinical Risk Score, originally developed to predict the occurrence of VTE, is also predictive of early mortality and cancer progression during the first four cycles of outpatient chemotherapy, independent from other major prognostic factors including VTE itself. Ongoing and future studies will help determine the impact of VTE prophylaxis on survival. Abstract : The authors applied the previously validated venous thromboembolism Clinical Risk Score to 4, 405 adults with solid tumors or lymphoma initiating chemotherapy. Risk scores were predictive of early mortality and cancer progression during the first four cycles of outpatient chemotherapy. High-risk patients had 120-day mortality rates of 12.7% and cancer progression rates of 27.2%; intermediate-risk patients, 5.9% and 16.4%, respectively; and low-risk patients, 1.4% and 8.5%.